2019
DOI: 10.1177/0959683619865593
|View full text |Cite
|
Sign up to set email alerts
|

Gradually increasing forest fire activity during the Holocene in the northern Ural region (Komi Republic, Russia)

Abstract: In many boreal regions of Russia the past natural variability of forest fire activity remains largely undocumented, preventing accurate assessment of the impact of current climate warming on forest ecosystem dynamics. This study aims to reconstruct the Holocene fire history of the northern Ural mountain foothills, in the Komi Republic, based on analyses of charcoal particles from peatland deposits and coupled with dendrochronological investigations. The results show that there was a gradual increase in forest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 100 publications
4
36
2
Order By: Relevance
“…Although some studies draw a similar conclusion (e.g. Carcaillet et al, 2001 in eastern Canada), this result contrasts with many other studies from the Eurasian and North American boreal zones, where vegetation changes were found to be closely connected to changes in fire regimes (Barhoumi et al, 2019(Barhoumi et al, , 2020Feurdean et al, 2020;Gavin et al, 2007;Kelly et al, 2013). However, on a shorter, multidecadal timescale, phases with more Cyperaceae pollen (sedges) in the Lake Khamra record and a higher ratio of evergreen to deciduous arboreal pollen types coincide with periods of high fire activity in phases 2 and 4 (see Fig.…”
Section: Vegetationcontrasting
confidence: 99%
See 3 more Smart Citations
“…Although some studies draw a similar conclusion (e.g. Carcaillet et al, 2001 in eastern Canada), this result contrasts with many other studies from the Eurasian and North American boreal zones, where vegetation changes were found to be closely connected to changes in fire regimes (Barhoumi et al, 2019(Barhoumi et al, , 2020Feurdean et al, 2020;Gavin et al, 2007;Kelly et al, 2013). However, on a shorter, multidecadal timescale, phases with more Cyperaceae pollen (sedges) in the Lake Khamra record and a higher ratio of evergreen to deciduous arboreal pollen types coincide with periods of high fire activity in phases 2 and 4 (see Fig.…”
Section: Vegetationcontrasting
confidence: 99%
“…The reconstructed record-wide mean FRI of 43 yrs, incorporating both the exceptionally short FRI of phase 2 (14 yrs) and the long FRI of phase 3 (60 yrs, excluding the c. 600-yr-long period without identified fires), lies within the range of the few comparable studies in western Siberia. Barhoumi et al (2019) found the shortest FRIs of the Holocene ranging from 40-100 yrs between 1500 CE and present day in macroscopic charcoal records from the northern Ural region. A mean FRI of 45 yrs during recent centuries was inferred by Feurdean et al (2020).…”
Section: Fire Regime History Of the Last Two Millennia At Lake Khamramentioning
confidence: 84%
See 2 more Smart Citations
“…At Yaksha, the three study sites did not show the same local recent fire activities when tree ring fire scars were analysed (Barhoumi et al, 2019). In Kuosmanen et al (2014)…”
Section: Boreal Biome Vegetation-fire Interactionsmentioning
confidence: 89%